The Relation between CRP and Ferritin in People Infected with COVID-19 in Al- Amariah City - Arkan Abdullah Abbas; Ban Mohammed Abbas Al-Kanan; Yasser Qassim Hussein (Institute of Medico-legal Publications Pvt Ltd, 2021)
he study aimed at the Covid-19 infection causes an increase in both the effective protein level C and the level of the ferritin of blood in the early diagnosis of COVID-19 infection. In the present study that was carried out in Amariah city from 15th of July to 15th of October 2020, a total of 100 people (60 infected group with COVID-19 and 40 control group without Covid-19) who were admitted to AL-Amariah Hospital whose ages were between 15-75 years. Patients were investigated for the detection of COVID-19 by using Real-Time PCR. The current study showed that the infection with COVID-19 is affected by the age factor of the patient. The highest rate of a patient with COVID-19 was within the age group >50 years with a highly significant relation between COVID-19 and age. The study showed that the highest rate of CRP in the infected group compared with a control group with a highly significant difference. The highest rate of ferritin in an infected group than the control group.